Advances in high-Tc grain boundary junctions: Сверхпроводимость и мезоскопические структуры - Tafuri, F.; Kirtley, J.R.; Lombardi, F.; Medaglia, P.G.; Orgiani, P.; Balestrino, G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
We review results on two novel types of grain boundary Josephson junctions in the high criticaltemperature cuprate superconductors. The quality of YBa2Cu3O7-d biepitaxial grain boundary Josephson junctions have been improved using a new growth geometry to the point that «tunnel-like» characteristics are reproducibly obtained. The consequent low barrier transmission probabilities are apparently favourable to isolate intrinsic d-wave induced effects. We also focus on peculiar aspects of spontaneous currents in HTS Josephson junctions, which are unique and reflect the intimate relation between vortex matter and the Josephson effect. Bicrystal grain boundary Josephson junctions have also been fabricated using artificial superlattice films with as few as sixsuperconducting copper–oxygen planes. Extrinsic and intrinsic d-wave effects in these junctions are discussed within the framework of novel designs for p-circuitry and qubits.